Application of charcoal-based monatomic iron catalyst in microbial fuel cell
By using biochar-based single-atom iron catalyst in microbial fuel cells, the problem of slow kinetic process and high overpotential of the cathode oxygen reduction reaction is solved, the effect of high voltage and high current density is achieved, and the cost is reduced, which is suitable for industrial production and environmental pollution control.
Patent Information
- Application Number
- CN202411828935.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
In existing microbial fuel cells, the slow kinetics of oxygen reduction reactions on the cathode and the high overpotential are the main obstacles to achieving high current density, and commercial Pt/C catalysts have limited their wide application due to their high cost and low reserves.
The biochar-based single-atom iron catalyst is used as the active ingredient of the cathode catalytic layer of the microbial fuel cell. The porous slag biochar is prepared by pyrolysis treatment of high-temperature oxygen-limited pyrolysis, and then mixed with iron salt and chelating agent to perform high-temperature pyrolysis to obtain the biochar-based single-atom iron catalyst.
It has achieved high electrocatalytic activity, improved the voltage and current density of microbial fuel cells, reduced the cost of raw materials, is suitable for large-scale industrial production, and has wide application prospects in the fields of sewage treatment and wetland protection.
Smart Images

Figure CN119650734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to the application of a biochar-based single-atom iron catalyst in a microbial fuel cell. Background Art
[0002] Energy crisis and environmental issues highlight the urgent need to transition from fossil fuels to renewable energy. Microbial fuel cells (MFCs) directly generate electricity through the metabolism of biodegradable organic matter by microorganisms under anaerobic conditions, which is in line with the concept of environmental sustainable development.
[0003] However, after microorganisms transfer electrons from the anode to the cathode through extracellular electron transfer, the slow oxygen reduction reaction (ORR) kinetics and high overpotential at the cathode are the main obstacles to achieving high current density in MFCs. Pt / C catalysts are considered to be the most advanced commercial electrocatalysts due to their excellent ORR activity. However, their high cost and low reserves limit their widespread application.
[0004] In recent years, single atom catalysts (SACs) have developed rapidly in the field of ORR. It has been shown that the carbon-based matrix has a strong structural effect on the performance of single atom catalysts. However, due to the expensive nature of the catalyst materials and their supporting carbon matrix, the synthesis cost of single atom catalysts is very high, which greatly restricts their application in microbial fuel cells.
[0005] Therefore, it is urgent to develop a new type of biochar-based single-atom catalyst that can be used in microbial fuel cells. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a biochar-based single-atom iron catalyst for use in microbial fuel cells.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] Application of a biochar-based single-atom iron catalyst in a microbial fuel cell, wherein the biochar-based single-atom iron catalyst is used as an active component of a cathode catalyst layer of the microbial fuel cell;
[0009] The biochar-based single-atom iron catalyst is prepared by the following method:
[0010] S1: subjecting the biogas residue powder to a first high-temperature oxygen-limited pyrolysis to obtain biogas residue biochar;
[0011] S2: mixing the biogas residue biochar with the pore-enlarging agent and subjecting it to a second high-temperature oxygen-limited pyrolysis to obtain porous biogas residue biochar;
[0012] S3: mixing the iron salt and the chelating agent to obtain a complex, mixing the complex with the porous digestate biochar and then drying;
[0013] S4: Evenly mix the dried powder with the cyanamide compound, and perform high-temperature pyrolysis to finally obtain the biochar-based single-atom iron catalyst.
[0014] Furthermore, in step S1, the raw material of the biogas residue is the product of anaerobic digestion of food waste.
[0015] Furthermore, the particle size of the biogas residue is 0.5-6 mm, preferably 0.5-1.5 mm.
[0016] Furthermore, in step S1, the biogas residue is dried, crushed and sieved in sequence to obtain biogas residue powder.
[0017] Furthermore, the sieve has a particle size of 100-200 meshes, preferably 100 meshes.
[0018] Furthermore, in step S1, the temperature of the first high-temperature oxygen-limited pyrolysis is 600-900°C and the time is 1-4h.
[0019] Furthermore, in step S2, the pore expanding agent is potassium hydroxide.
[0020] Furthermore, in step S2, the mass ratio of the sludge biochar to the pore expanding agent is 1:(1-3).
[0021] Furthermore, in step S2, the temperature of the second high-temperature oxygen-limited pyrolysis is 700-900°C and the time is 1-4h.
[0022] Furthermore, in step S3, the molar ratio of the iron salt to the chelating agent is 1:(1.5-4), preferably 1:4.
[0023] Furthermore, the chelating agent is 1,10-phenanthroline.
[0024] Further, in step S3, the mass ratio of the molar amount of the iron salt to the porous biogas residue biochar is 1 mol:
[0025] 200-600mg, preferably 1mol:500mg.
[0026] Furthermore, in step S3, the mass ratio of the dried powder to the cyanamide compound is 0.2:(1-2), preferably 0.2:2.
[0027] Furthermore, the cyanamide compound includes one or more of melamine and dicyandiamide, preferably melamine.
[0028] Furthermore, the first high-temperature oxygen-limited pyrolysis and the second high-temperature oxygen-limited pyrolysis are both carried out in a protective atmosphere.
[0029] Furthermore, in step S4, the temperature of the high temperature pyrolysis is 700-900°C; the heating rate is 4-6°C / min, preferably 5°C / min; and the time is 1-6h.
[0030] Furthermore, the cathode catalyst layer of the microbial fuel cell is prepared by the following method:
[0031] The biochar-based single-atom iron catalyst, zirconium dioxide and polymer solution are mixed and stirred evenly, and then coated on the cathode material and dried to obtain the microbial fuel cell cathode catalyst layer containing the biochar-based single-atom iron catalyst.
[0032] Furthermore, the mass ratio of the biochar-based single-atom iron catalyst to zirconium dioxide is 1:(15-25), preferably 1:20.
[0033] Furthermore, the loading amount of the cathode catalyst layer of the microbial fuel cell is 1-2 mg / cm 2 .
[0034] Furthermore, the polymer is a perfluorosulfonic acid type polymer.
[0035] Furthermore, the cathode material is carbon cloth.
[0036] Furthermore, the biochar-based single-atom iron catalyst, zirconium dioxide and polymer are dissolved in an alcohol solution, followed by stirring for 2-4 hours, preferably 2 hours; and then ultrasonically dispersed for 10-30 minutes, preferably 15 minutes.
[0037] Furthermore, the alcohol solution is an isopropanol aqueous solution.
[0038] Furthermore, the volume ratio of the isopropanol, water and 20%wt Nafion solution is (4.5-5.0):1:(0.04-0.06).
[0039] Furthermore, the drying temperature is 60-80°C, preferably 70°C.
[0040] Furthermore, the drying time is 6-8 hours.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The present invention successfully prepared a biochar-based single-atom iron catalyst that can be used as a cathode catalyst for a microbial fuel cell using biomass sludge and iron salt as raw materials. The biochar-based single-atom iron catalyst has high electrocatalytic activity, and the microbial fuel cell finally prepared has higher voltage and current density than commercial Pt / C catalysts.
[0043] (2) The present invention uses waste biomass sludge as raw material to produce an efficient microbial fuel cell cathode catalyst. The raw material cost is low and the preparation process is simple, which is suitable for industrial-scale production.
[0044] (3) The cathode catalyst of the microbial fuel cell prepared by the present invention has high electrocatalytic activity and good stability, and has broad application prospects in environmental fields such as microbial fuel cells, sewage treatment, and wetland protection.
[0045] (4) The present invention uses sludge as a raw material for preparing biochar. As a waste product of anaerobic digestion, sludge can be effectively used as a raw material for preparing biochar and added to a pollutant control system to form a synergistic treatment of raw materials and environmental pollution, providing a solution for effectively treating waste and controlling environmental pollution at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a TEM image of the biochar-based single-atom iron catalyst prepared in Example 1 of the present invention.
[0047] Figure 2 This is a disassembled diagram of the working parts of the microbial fuel cell according to Example 1 of the present invention.
[0048] Figure 3 The power density and polarization curves of the microbial fuel cells in the embodiments and comparative examples are shown.
[0049] Figure 4 Graph showing the COD and ammonia nitrogen degradation rates of the microbial fuel cells in the examples and comparative examples. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0051] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0052] Embodiment 1:
[0053] This embodiment provides a biochar-based single-atom iron catalyst and a microbial fuel cell cathode catalyst layer, and the specific preparation method is as follows:
[0054] (1) Preparation of biochar-based single-atom iron catalysts
[0055] 10 g of biogas residue (with a particle size of 0.5-6 mm) derived from the anaerobic digestion of food waste was dried, crushed in a grinder, and passed through a 100-mesh sieve to obtain biogas residue powder; the powder was transferred to a crucible for compaction, and pyrolyzed at 600°C for 2 h in oxygen-limited condition to obtain biogas residue biochar.
[0056] 10 g of the above-mentioned biochar was mixed with 10 g of potassium hydroxide, ground in a ball mill for 4 h, transferred to a crucible for compaction, and pyrolyzed at 800 °C for 2 h in oxygen-limited condition to obtain porous biochar.
[0057] 0.5 mol of ferric acetate and 2 mol of 1,10-phenanthroline were accurately weighed, added to 25 ml of ethanol, and slowly stirred at 65 °C for complexation. The obtained complex was mixed with 250 mg of the above-mentioned porous biochar and dried. 0.2 g of the dried powder was fully ground with 2 g of melamine, and the mixed powder was transferred to 100 ml / min of nitrogen for high-temperature pyrolysis at a heating rate of 5 °C / min for 2 h, and then cooled to room temperature to obtain a biochar-based single-atom iron catalyst, recorded as Fe-SA / NBC.
[0058] Figure 1 TEM image of the biochar-based single-atom iron catalyst prepared in this example. Figure 1 As shown in the figure, the single-atom iron catalyst based on porous biomass carbon presents a groove-ridge shape, which is related to its large specific surface area. In addition, no obvious iron crystal clustering phenomenon is observed, and the surface iron atoms are dispersed on the surface of biochar.
[0059] (2) Preparation of cathode catalyst layer of microbial fuel cell
[0060] In this embodiment, carbon cloth is used as the cathode material, and a catalytic layer is prepared on the carbon cloth. First, weigh the carbon cloth and record the weight. Weigh 1332 mg of zirconium dioxide and 66.6 mg of biochar-based single-atom iron catalyst and transfer them into a beaker. Add 8.22 ml of isopropanol, 1.7 ml of deionized water, and 80 ul of 20% wt Nafion solution to the beaker, seal it and stir it magnetically for 2 hours, then ultrasonically disperse it for 15 minutes to obtain a dispersed catalyst suspension. The catalyst suspension is evenly coated on the back of the carbon cloth, dried naturally and dried at 70 ° C for 6 hours to obtain a fully prepared cathode carbon cloth containing the catalyst. According to the mass difference before and after drying the carbon cloth, the weight of the catalyst actually loaded on the cathode is calculated. The loading capacity of the cathode catalyst layer of the microbial fuel cell in this embodiment is 1.4 mg / cm2 .
[0061] like Figure 2 As shown, the MFC configuration used in this embodiment is a single-chamber MFC. The inoculum solution uses the effluent from an anaerobic tank of a sewage treatment plant. In the experiment, the sewage was aerated in nitrogen for more than 12 hours to maintain an anaerobic environment and provide the required environment for microorganisms. At the beginning of the experiment, the anode was composed of a commercial carbon brush, and the cathode was a carbon cloth coated with a catalyst prepared in this embodiment. The growth medium consisted of sodium acetate (2g / L), vitamin solution (5mL / L), mineral solution (12.5mL / L) and PBS solution (50mM). After the configuration was completed, the sewage: growth medium was mixed at a ratio of 4:6 (volume ratio) and added to the single-chamber MFC. The cathode and anode were connected with titanium wire, and the external resistance was set to 1000Ω. Each catalyst was tested 2-3 times in a single-chamber MFC. All MFC reactors were kept at room temperature, and the voltage output per minute was recorded using a data acquisition instrument.
[0062] Embodiment 2:
[0063] This embodiment provides a biochar-based single-atom iron catalyst and a microbial fuel cell cathode catalyst layer. The difference from Example 1 is that in this embodiment, during the preparation of the biochar-based single-atom iron catalyst, the molar amount of ferric acetate is 0.5 mol, and the amount of porous biogas residue biochar is 200 mg.
[0064] Embodiment 3:
[0065] This embodiment provides a biochar-based single-atom iron catalyst and a microbial fuel cell cathode catalyst layer. The difference from Example 1 is that in this embodiment, during the preparation of the biochar-based single-atom iron catalyst, the molar amount of iron acetate is 1 mol and the amount of porous biogas residue biochar is 600 mg.
[0066] Embodiment 4:
[0067] This embodiment provides a biochar-based single-atom iron catalyst and a microbial fuel cell cathode catalyst layer. The difference from Example 1 is that in this embodiment, during the preparation of the microbial fuel cell cathode catalyst layer, the amount of zirconium dioxide used is 666.0 mg, and the amount of the biochar-based single-atom iron catalyst used is 33.3 mg.
[0068] Comparative Example 1:
[0069] The difference from Example 1 is that the cathode catalyst of this comparative example is a commercial 20 wt % Pt / C catalyst.
[0070] Comparative Example 2:
[0071] The difference from Example 1 is that the cathode catalyst of this comparative example is only biochar from biogas residue, denoted as BC. 10 g of biogas residue (with a particle size of 0.5-6 mm) from the anaerobic digestion of food waste was dried, crushed by a pulverizer, and passed through a 100-mesh sieve to obtain biogas residue powder; the biogas residue powder was transferred to a crucible for compaction, and pyrolyzed at 600°C for 2 h in oxygen-limited conditions to obtain biogas residue biochar.
[0072] The present invention conducts the following tests on the microbial fuel cells finally assembled from the above-mentioned embodiments and comparative examples:
[0073] (1) Polarization curve and power density test: The polarization curve and power density of MFC are tested by external resistance method. First, the MFC to be tested is stabilized in the open circuit state for 10-30 minutes, and then connected to a resistance box with different impedances (20-10000Ω). Each time the resistance is changed, it is stabilized for 10-30 minutes before recording the data. Then the voltage meter display data is read and the measured voltage is recorded.
[0074] The polarization curve and power density calculation formula of MFC are as follows:
[0075]
[0076] Wherein, R is the external variable resistor, U is the electromotive force under different R, A is the surface area of the cathode material; I is the current density, and P is the power density.
[0077] (2) Chemical oxygen demand (COD) test: Spectrophotometry was used to test chemical oxygen demand (COD). Take 10-20 ml of MFC water sample and centrifuge it at 10,000 rpm for 8 min. Take the centrifuged supernatant and filter it with a 0.45 um filter membrane. Take 0.5-2 ml of the resulting solution and add it to a commercial COD test kit for testing. Read the spectrophotometer reading and record it. The COD removal rate calculation formula is as follows:
[0078]
[0079] Among them, COD removal is the COD removal rate; COD in is the COD content of the influent; COD out is the effluent COD content.
[0080] (3) Ammonia nitrogen removal rate: The ammonia nitrogen removal rate was tested by salicylic acid method and spectrophotometry. Take 10-20 ml of MFC water sample and centrifuge at 10,000 rpm for 8 min. Take the centrifugal supernatant and filter it with a 0.45 um filter membrane. Take 0.5-2 ml of the resulting solution and add it to a special ammonia nitrogen detection kit for detection. Use a special spectrophotometer to read and record. The ammonia nitrogen removal rate calculation formula is as follows:
[0081]
[0082] NH 3 -N removal is the ammonia nitrogen removal rate; NH 3 -N in is the ammonia nitrogen content in the influent; NH 3 -N out Ammonia nitrogen content in effluent.
[0083] Figure 3 The polarization curve and power density comparison diagram of the microbial fuel cell after 30 days of operation are given. Figure 3 It can be clearly seen in a that the microbial fuel cell using the Fe-SA / NBC cathode produces a higher voltage and current density than the commercial Pt / C. The open circuit voltage of the entire circuit and the cathode are 0.72V and 0.2V for Fe-SA / NBC respectively. Voltage is an important indicator of microbial fuel cells. The higher the voltage, the better the effect of the fuel cell under the action of this catalyst. In addition, from Figure 3 It can be found in b that the maximum power density of Fe-SA / NBC is 1.23 times that of the commercial Pt / C catalyst, indicating that the external output power of Example 1 is the highest. The higher the output power density of the microbial fuel cell, the higher the power that the fuel cell can provide in practical applications.
[0084] Figure 4 The removal rates of chemical oxygen demand (COD) and ammonia nitrogen by the microbial fuel cells of Example 1 and the comparative example are shown. It can be clearly seen from the figure that the removal rate of COD by the cathode microbial fuel cell with Fe-SA / NBC as the catalyst (≈47.80%) is better than that of Pt / C (≈40.91%); the ammonia nitrogen removal rate of Fe-SA / NBC is 1.02 times that of Pt / C, and the removal efficiency of both is better than that of the biochar in Comparative Example 2 (≈88.10%).
[0085] The above results show that the microbial fuel cell cathode catalyst Fe-SA / NBC prepared in the present invention not only has excellent performance in energy generation, but also can provide excellent functions in the field of coordinated sewage treatment, indicating that it has broad application prospects as a dual-purpose catalyst.
[0086] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. Application of a biochar-based single-atom iron catalyst in a microbial fuel cell, characterized in that: The biochar-based single-atom iron catalyst is used as an active component of the cathode catalyst layer of a microbial fuel cell; The biochar-based single-atom iron catalyst is prepared by the following method: S1: subjecting the biogas residue powder to a first high-temperature oxygen-limited pyrolysis to obtain biogas residue biochar; S2: mixing the biogas residue biochar with the pore-enlarging agent and subjecting it to a second high-temperature oxygen-limited pyrolysis to obtain porous biogas residue biochar; S3: mixing the iron salt and the chelating agent to obtain a complex, mixing the complex with the porous digestate biochar and then drying; S4: Evenly mix the dried powder with the cyanamide compound, and perform high-temperature pyrolysis to finally obtain the biochar-based single-atom iron catalyst.
2. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S1, the raw material of the biogas residue is the product of anaerobic digestion of food waste, and the particle size of the raw material of the biogas residue is 0.5-6 mm; The biogas residue is dried, crushed and sieved in sequence to obtain biogas residue powder; wherein the sieve mesh particle size is 100-200 mesh.
3. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S1, the temperature of the first high-temperature oxygen-limited pyrolysis is 600-900°C and the time is 1-4 hours.
4. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S2, the pore expanding agent is potassium hydroxide; The mass ratio of the sludge biochar to the pore expanding agent is 1:(1-3).
5. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S2, the temperature of the second high-temperature oxygen-limited pyrolysis is 700-900°C and the time is 1-4 hours.
6. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S3, the molar ratio of the iron salt to the chelating agent is 1:(1.5-4), and the chelating agent is 1,10-phenanthroline; The mass ratio of the molar amount of the iron salt to the porous biogas residue biochar is 1 mol: 200-600 mg; The mass ratio of the dried powder to the cyanamide compound is 0.2:(1-2).
7. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: In step S4, the high temperature pyrolysis temperature is 700-900°C, the heating rate is 4-6°C / min, and the time is 1-6h.
8. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 1, characterized in that: The cathode catalyst layer of the microbial fuel cell is prepared by the following method: The biochar-based single-atom iron catalyst, zirconium dioxide and polymer solution are mixed and stirred evenly, and then coated on the cathode material and dried to obtain the microbial fuel cell cathode catalyst layer containing the biochar-based single-atom iron catalyst.
9. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 8, characterized in that: The mass ratio of the biochar-based single-atom iron catalyst to zirconium dioxide is 1:(15-25); The polymer is a perfluorosulfonic acid type polymer; The loading amount of the cathode catalyst layer of the microbial fuel cell is 1-2 mg / cm 2 .
10. The use of a biochar-based single-atom iron catalyst in a microbial fuel cell according to claim 8, characterized in that: The biochar-based single-atom iron catalyst, zirconium dioxide and polymer are dissolved in an alcohol solution, then stirred for 2-4 hours, and ultrasonically dispersed for 10-30 minutes; The drying temperature is 60-80° C. and the drying time is 6-8 hours.
Citation Information
Patent Citations
Preparation method of ultrathin flexible carbon nanosheet oxygen reduction catalyst based on anaerobic fermentation biogas residues
CN111129523A
Biomass waste residue-based monatomic metal catalyst as well as preparation method and application thereof
CN114210331A
Iron-attached carbon powder as well as preparation method and engineering application thereof
CN116553717A